Burnout in general practice. Issue 6 (June 2016) - Jones, Daniel; Davies, Peter
Workload pressures on GPs are increasing, due to an increasing number of patients requiring attention and the extended periods that they are now living with multiple, complex chronic conditions. In addition, the recruitment and retention of GPs in the UK is falling; at the time of writing this article, these factors have led the profession to be described as being in a state of crisis. In 2015, the RCGP estimated that there was a shortfall of over 3000 GPs. With this in mind, there is increasing concern about the mental and physical health of the workforce, and the sustainability of the speciality and its workload. This article will look at burnout, what it is, its prevalence in the medical profession and what help is available.